Strategic guidelines for the development of UTС finances: implementation of world experience - Kneysler, Olga; Spasiv Nataliіa (Herald of Economics, 2020)
Introduction. In the context of reforming the system of local self-government and territorial organization of power, the use of world best practices in the context of decentralization and implementation of best foreign practices in shaping the finances of territorial communities and their associations is of paramount importance. Accordingly, a number of important theoretical postulates of domestic financial science need to be reconsidered through the prism of improving existing and developing the latest conceptual approaches to the functioning of the finances of united territorial communities (OTG) using international advances in this area. local development.Purpose. Given the limited theoretical and practical work of domestic scholars on the finances of the united territorial communities, the purpose of the article is to use the best world practices to improve the efficiency of OTG finances.Methods. The methodological basis of the study are general scientific and economic- statistical methods: analysis, synthesis, statistical method - to study the international experience of OTG finance reform; inductions, deductions - to determine the directions of development of OTG finances in Ukraine; abstract-logical, economic-mathematical - for estimating revenues and expenditures of local budgets of OECD countries. Results. The world experience of reforming the finances of territorial communities is considered. In the context of application of the best international practices the directions of development of finance of OTG in Ukraine under modern conditions of carrying out financial decentralization are offered. Estimates of revenues and expenditures of local budgets of OECD countries were assessed, which allowed to determine priorities in revenue generation, expenditure optimization, distribution of powers and functions, as well as the use of new sources to increase the revenue base of local communities and their associations in Ukraine. Discussion. The prospects for further research is to develop a model for optimizing the financing of OTG development in order to ensure the implementation of its own powers and functions.